The Comprehensive Systematic Review of Relationship between Prophylactic Anticoagulant Administration and Prevention of Thromboembolism in Hospitalized Heart Failure Patients - Cassandra Savira Alisa; Miftahul Afandi; Yoga Alfian Noor (The International Journal of Medical Science and Health Research, 2026)
Introduction: Hospitalized heart failure (HF) patients face heightened thromboembolic risk, yet the net benefit of prophylactic anticoagulation remains debated. This systematic review evaluates the positive significant evidence for anticoagulant prophylaxis in preventing thromboembolism in hospitalized HF patients. Methods: We screened RCTs involving hospitalized HF patients receiving prophylactic anticoagulation (heparins, LMWH, fondaparinux, rivaroxaban, warfarin) versus comparator, reporting thromboembolic outcomes. Data extraction focused on significant positive efficacy and safety findings. Results: In acute HF, fondaparinux reduced VTE by 46.7% (95% CI 7.7–69.3%; P=0.029) with 0.2% major bleeding [1]. Extended rivaroxaban 10 mg in HF (MAGELLAN) reduced VTE by 36% (RR 0.64, 95% CI 0.44–0.93; P=0.018; NNT=50) in low-bleeding-risk patients [4]. In chronic HF with sinus rhythm, rivaroxaban 2.5 mg (COMMANDER HF) reduced stroke/TIA by 32% (HR 0.68, 95% CI 0.49–0.94; NNT=164/year) [7] and thromboembolic events including sudden death by 17% (HR 0.83, 95% CI 0.72–0.96; P=0.01) [22]. Among patients with D-dimer >515 ng/mL, rivaroxaban reduced stroke by 64% (HR 0.36, 95% CI 0.18–0.70; NNT=36) [10]. In HF with atrial fibrillation, rivaroxaban reduced hemorrhagic stroke (HR 0.38, 95% CI 0.19–0.76) [12], and apixaban reduced stroke/systemic embolism or death (HR 0.89, 95% CI 0.81–0.98; P=0.02) [13]. For left ventricular thrombus, DOACs reduced stroke/thromboembolism (log OR −2.02; NNT=12.5) and bleeding (NNT=10.6) versus warfarin [14]. In acute HF, oral anticoagulation reduced 30-day mortality (HR 0.73, 95% CI 0.59–0.90) [47]. In post-ACS HF patients, rivaroxaban 2.5 mg reduced CV death/MI/stroke by 41% (HR 0.59, 95% CI 0.42–0.81; P=0.001) [67]. Discussion: Positive significant findings concentrate in identifiable high-risk subgroups: acute hospitalization, elevated D-dimer, atrial fibrillation, left ventricular thrombus, and post-ACS settings. Biomarker-guided (D-dimer) and age-specific strategies optimize net clinical benefit. Conclusion: Prophylactic anticoagulation significantly reduces thromboembolism in hospitalized HF patients, particularly when guided by biomarkers, thrombotic context, and bleeding risk assessment. Routine use in acute HF and targeted use in chronic HF with high-risk features is supported.